Effects of the Ionizing Radiation Disinfection Treatment on Historical Leather - Vadrucci, Monia; De Bellis, Giovanni; Mazzuca, Claudia; Mercuri, Fulvio; Borgognoni, Fabio; Schifano, Emily; Uccelletti, Daniela; Cicero, Cristina (Frontiers in Materials, 2020)
Microorganisms often cause significant damage on historical objects. The archive or library materials 24 as well as textile or leather artifacts suffer serious attacks that need appropriate care treatments. 25 Several biocide processes have been implemented but often their application does not preserve the 26 material of the good. The objective of this work is the disinfection through ionizing radiation of 27 leather wallpaper from the museum building Palazzo Chigi in Ariccia (Rome, Italy). The controlled 28 sterilization treatments were carried out using X-ray beams to eliminate the microorganisms present 29 on the leather and maintaining unchanged the properties of the constituent material. Some fragments 30 of decorated leather wallpaper, dating back to the 1700s, were irradiated with X-rays up to 5000 Gy. 31 The amount of microorganisms was evaluated by microbiological analysis before and after X-ray 32 irradiation treatments to identify the dose that inhibits the bacterial load. It will be shown how the 33 results obtained by the application of different chemical-physical techniques (Scanning Electron 34 Microscopy, Fourier Transform Infrared spectroscopy and Light Transmission Analysis) have helped 35 in the evaluation of the impact of the X-rays on leather chemical and physical integrity.